STUDENTS’ PERCEPTION ON LEADERSHIP SKILLS VIA GROUP WORK IN AN ESL CLASSROOM IN HIGHER LEARNING INSTITUTION - Irma Wani Othman; Mohd Sohaimi Esa; Saifulazry Mokhtar; Anna Lynn Abu Bakar; Romzi Ationg; Mohd Kamal Mohd Shah; Nurul Ain Zulhaimi (Journal of Islamic, Social, Economics and Development, 2021)
Leadership skills could be developed and enhanced through group work in an ESLclassroom. Working in groups enables students to develop and apply their leadership skills inmanaging their group members. It is important for English Language Instructors to provide theopportunity for students in the ESL classroom to not only be able to communicate interactivelyin English among their group members but also able to learn the skills in managing the group.Thu, this study aims to investigate the students’ perception on leadership while working ingroups. A qualitative approach that utilises a semi structed interview was conducted on 45participants from 6 different classes. The findings of this study revealed three main areas thatthe participants perceived influences their leadership skills when working in groups. The twomain areas are 1) the challenges that they face when managing a group and 2) the solutionsthat they took to overcome the challenges. The findings of this study are useful not only toEnglish language instructors but also to students in order to have a better understanding on the issues that were faced by the students in managing a group in an ESL classroom in HigherLearning Institution.